TEACHERS’ MOTIVATIONS, BELIEFS, AND EXPECTATIONS REGARDING MORAL EDUCATION IN UPPER SECONDARY EDUCATION - Fernández González, Manuel Joaquín; Mūrnieks, Andrejs; Vējiņš, Reinis; Sidorova, Anna; Elksne, Gunita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
This study explored high school teachers’ motivations and preferences regarding adolescents’ moral education in the context of the assessment of the newly developed program ‘e-TAP+’ for virtue education in Grades 10 to 12 in Latvia. The program comprises four modules: personal flourishing, flourishing relationships, societal flourishing, and digital flourishing. The research questions guiding the research were: Which aspects of moral education at high school were most important for teachers, as evidenced by the topics they chose to pilot in their classes? What were teachers' motivations for and expectations of participating in the evaluation of the virtue education program? This mixed-method survey research used an online questionnaire completed by 107 secondary school teachers from all regions of Latvia. In December 2023 – January 2024 teachers volunteered to participate in the piloting of the program, chose their preferred topics, and provided open-ended feedback on their choices and motivations. A total of 225 topics were chosen (90 in Grade 10, 81 in Grade 11, and 54 in Grade 12). Preliminary findings suggest that participants’ overall opinion about the program was very positive. Teachers’ main motivations were (1) the availability of quality materials for classroom discussion about virtues and values, and (2) the topicality of the program’s themes. Teachers in Grade 10 prioritized topics related with flourishing relationships (n=29, 32%), teachers in Grade 11 had a slightly bigger interest in personality than in relationships (n=28, 34% and n=24, 30%, respectively), and teachers in Grade 12 prioritized personality flourishing (n=20, 37%). The results will be valuable for other high school teachers and leaders, organizers of professional development courses, policymakers and other education authorities, and moral education researchers.